Kawin-Cerai Hidup dan Kawin Lagi Dari Sudut Pandang Hukum Kanonik Gereja Katolik dan Sumbangsihnya Bagi Karya Pastoral di Paroki St. Markus Melak Keuskupan Agung Samarinda - Jegaut, Siprianus; Fernandes, Stefanus (Perspektif, 2024)
The focus of this study is "Marriage, Divorce, and Remarriage from the Point of View of the Canonical Law of the Catholic Church and Its Contribution to Pastoral Work in the Parish of St. Mark Melak Archdiocese of Samarinda”. Because marriage is a very important matter, the Church, state, and traditional institutions regulate it respectively. The Catholic Church regulates it in the Code of Canon Law, specifically Canons 1055-1165. Catholic marriage is always reviewed from natural, ecclesiastical, and civil law. Natural Law applies to everyone without exception, including those from other religions or other cultures. This study aims to explain the basic reasons why the Catholic Church does not confirm marriages from other churches which are still bound by previous marriages with Catholics who do not experience legal obstacles. The method used is phenomenology and literature. This study found that natural law is the basic reason for those who are still previously married not getting married. Second, the marriage of the baptized is considered as a sacrament by canon law.